Characterization and antioxidant activity of pectin from Indonesian mangosteen (Garcinia mangostana L.) rind - Nasrul Wathoni; Chu Yuan Shan; Wong Yi Shan; Tina Rostinawati; Raden Bayu Indradi; Rimadani Pratiwi; Muchtaridi Muchtaridi (Heliyon, 2019)
Pectin, a natural polysaccharide, has gained increasing attention due to not only its biomaterial properties but also its biomedical activities. One of the abundant sources of pectin is mangosteen (Garcinia mangostana L.) rind. In this study, we characterized the pectin from Indonesian mangosteen rind extract and evaluated its antioxidant activity. Pectin was extracted in acid condition and evaluated its physicochemical properties by fourier transform infrared (FTIR), powder X-ray diffractometer (PXRD), water content, ash content, equivalent weight, methoxyl level and of galacturonic acid content. Furthermore, the antioxidant activity of pectin was also observed by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Pectin was successfully extracted from dry weight of Indonesian mangosten rind with yield about 1,16 ± 0,17%, fine powder, brownish and odorless. FTIR and PXRD results showed that pectin from mangosteen rind extract was amorphous and similar characteristic with a commercial pectin. The chemical properties of pectin such as water content, ash content, equivalent weight, methoxyl level and of galacturonic acid level were 9.85 ± 0.12%, 3.91 ± 0.17%, 6330.76 ± 220.43 g/mol, 2.86 ± 0.05% and 75.98 ± 0.88%, respectively. In addition, pectin showed an antioxidant activity with the IC50 about 161.94 ± 31.57 ppm. These results suggest that pectin from Indonesian mangosteen rind has the potential properties as biopolymers for biomedical applications with a low-methylated pectin and a moderate antioxidant activity.